Alunos com deficiência mental incluídos no ensino regular em município do Litoral Norte paulista - Gomes, Enaida Rodrigues (2006)
The present study investigated the student's inclusion with deficiency in the schools common of basic education in municipal district of the coast north from São Paulo, focalizing the access to the and support to the student with mental deficiency of the classes from 1st to 4th series of the Fundamental Teaching. It is known that the student's inclusion with deficiency is right constituted in the public politics of the Brazilian education. In that sense, guidelines and norms were analyzed from the referring education to the spheres federal, state and municipal, as well as, relative bibliography to the theme. I tried to map the students' distribution with deficiency physical, sensorial, mental and multiple, in order to analyze the conformity among the enunciated beginnings, the organization and attendance offered in the municipal net of education. The documental analysis it indicated that the student's inclusion with mental deficiency, implicates to add responsibilities of all, of the professionals of the teaching net, of the professionals of the schools in all the actions, beginning with the student's identification in the intention of implementing attendance to your school needs, such as special educational resources that guarantee the quality education for all.